The Role of Baitul Mal in Financing Dayah Education in Aceh Singkil Regency and Subulussalam City Government - B., Muhammad Saripudin; Mukti, Abd.; Sapri, Sapri (Pascasarjana Universitas KH. Abdul Chalim, 2024)
The role of Baitul Mal in financing Dayah education in Aceh Singkil Regency and Subulussalam City faces several problems, including the limited and uneven allocation of ZIS funds for Dayah, especially in remote areas, the lack of coordination and transparency in fund distribution hampers the effectiveness of distribution, and low public awareness of ZIS contributions to Dayah education reduces the potential for fundraising. This study uses a library research method. The main data sources in this study are reference books that discuss Baitul Mal, zakat, infaq, sedekah (ZIS), and Dayah education. The findings underscore that (1) Baitul Mal in Aceh Singkil and Subulussalam channels ZIS contributions through mosques, zakat agencies, and digital platforms, yet dedicates only 20–30 percent to Dayah, resulting in uneven distribution and limited transparency; (2) further optimization is impeded by weak coordination with Dayah administrators, opaque distribution processes, limited public awareness of ZIS’s impact on Dayah education, and constrained administrative capacity; and (3) the allocated funds have fostered meaningful improvements—upgrading facilities, empowering teachers through professional development, refining curricula, and awarding scholarships to deserving students.